An optimised injection technique for the navicular bursa that avoids the deep digital flexor tendon. (25th February 2015) - Daniel, A. J.; Goodrich, L. R.; Barrett, M. F.; Werpy, N. M.; Morley, P. S.; McIlwraith, C. W.
Summary: Reasons for performing study: Injection of the navicular bursa is commonly performed from the palmar aspect of the limb, which results in penetration of the deep digital flexor tendon (DDFT). Objectives: To report a radiographic guided injection from the lateral aspect of the limb that avoids puncture of the DDFT and to assess synovial and soft tissue penetration by the needle. Study design: Prospective clinical and cadaveric study. Methods: Prospective analysis of cadaver limbs and clinical cases in which the navicular bursa was injected from the lateral aspect. Cadaver limbs were placed in a stand to simulate weight bearing and injection was performed in limbs without synovial distension or with distension of either the distal interphalangeal (DIP) joint, digital flexor tendon sheath (DFTS) or navicular bursa. In cadaver and clinical limbs, contrast was injected and the needle position assessed with radiographs. Cadaver (but not clinical) limbs were also examined using magnetic resonance imaging with the needle in situ . Results: Successful navicular bursal injection was achieved in all limbs (n = 71). Relative risk of DIP joint puncture was 19 times higher (95% confidence interval 1.3–285.4, P<0.001) when the DIP joint was distended (9 of 10 limbs) than in normal limbs (0 of 10 limbs). Relative risk of DFTS puncture was 2.7 times higher (95% confidence interval 1.0–7.2, P = 0.06) when the DFTS was distended (8 of 10 limbs) than in normal limbs (3 of 7 limbs). Synovial fluid was aspirated from 47% of bursae from clinical cases. Conclusions: The lateral injection technique for the navicular bursa avoids penetration of the DDFT, although risk of synovial penetration must be considered when there is potential DIP joint or DFTS infection.